Comparative composition of fecal contents between broiler ducks and village chickens - Chong, Chiew Foong (2016)
Compositions of fecal contents and feed between broiler ducks (Cherry Valley) and village chickens reared at the Perak Duck Food Sdn. Bhd and a small scale village chicken farm were investigated. A total of 25 grams of fecal sample of adult broiler ducks and village chickens were collected respectively. Proximate analysis was carried out to analyze the moisture, dry matter, ash and crude protein using Kjedahl method contents in the fecal and feed samples using official method of AOAC. Statistical analysis was performed using the data collected by SPSS statistical software. Result from the proximate analysis of feed reveals there is statistically significance (P<0.05) different for the percentage of moisture contents. The moisture content in chicken broiler starter crumble mixed with corn is 9.8±0% while in duck broiler finisher pellet is 9.16±0.03% but there is no statistically significance (P>0.05) different in percentage of dry matter, ash and crude protein content between chicken broiler starter crumble mixed with corn and duck broiler finisher pellet. The dry matter is 90.2±0% and 90.8±0%, ash is 4.43±0.63% and 5.23±0.83% and crude protein is 21.73±0.81% and 19.92±1.22% in chicken broiler starter crumble mixed with corn and duck broiler finisher pellet respectively. The results for the proximate analysis of fecal samples is that there is statistically significance (P<0.05) different for the percentage of ash contents which is 1.06±0.12% in village chicken feces and 3.133±0.49% in Cherry Valley duck feces but there is no statistically significance (P>0.05) different in percentage of moisture, dry matter, ash and crude protein content between feces of village chicken and Cherry Valley. The moisture is 75.56±1.31% and 72.4±1.91% , the dry matter is 24.43±1.13% and 27.6±1.91% while the crude protein is 7.47±0.37% and 8.6±0.99% respectively in feces of village chicken and Cherry Valley ducks. The results for the digestibility of feed is that there is no statistically significance (P>0.05) different in digestibility of dry matter and crude protein content between village chicken and Cherry Valley duck. The digestibility of dry matter is 72.91±1.25% and 69.6±2.1%, the digestibility of crude protein is 65.64±0.39% and 56.77±4.37% in village chicken and Cherry Valley ducks respectively.